Supportive care needs of adolescents and young adults 5 years after cancer: a qualitative study - Baudry, Valentine; Girodet, Magali; Lochmann, Mathilde; Bottichio, Margaux; Charton, Emilie; Flahault, Cécile; Baudry, Anne-Sophie; Bertrand, Amandine; Christophe, Véronique (Frontiers in Psychology, 2024)
Adolescents and young adults (AYA) survivors who have been treated for cancer during childhood and adolescence are at great risk of the physical, psychological, and social consequences of cancer and its associated treatments. However, compliance with long-term follow-up is low. One possible explanation is that follow-up care fails to meet the expectations of AYA survivors. This study explored the specific supportive care needs of AYA survivors of childhood and adolescent cancer in follow-up five years post-diagnosis.Semi-structured interviews were conducted with 15 AYA aged 15 to 25 years old. Thematic analyses were conducted to establish categories of supportive care needs and classify them as being met or unmet.Participants reported between 2 and 20 specific needs (M = 11), including needs concerning fertility issues and reassurance regarding relapse (each mentioned by 67% of AYA), followed by the need for locomotor care, follow-up coordination and multidisciplinary care (60% of AYA for each). Participants also reported needs regarding social relationships, administration and finance, and academic and professional domains. Most (69%) of these needs were reportedly unmet, including need of information about cancer repercussions and follow-up, support in managing fatigue and sleep problems, psychological assistance, and support from peers.The supportive care needs are still considerable and varied in AYA survivors of childhood and adolescent cancer 5 years post-diagnosis and are largely unmet. As unmet supportive care needs highlight the gap between available care in follow-up and the real needs of AYA survivors, a better understanding of their supportive care needs and unmet needs, thanks to systematic needs assessment, would enable long-term follow-up care to be adapted, thereby improving compliance and quality of life.